The Role of Women in Creating Indonesia's Golden Generation 2045: Penelitian - Wilda Sumarsyah; Diah Apriliani; Bambang Amir Alhakim; Priyono Sadjijo; Romuadus Antonius Geli Koten (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a qualitative study with a descriptive approach, namely an approach that has descriptive narrative characteristics to the main topics in this study which include the Role of Women, Gender Roles, and Indonesia EMAS 2045. The data used in this study are secondary data that researchers obtained from various credible sources such as scientific articles, books, and so on which are commonly used in every study. The data obtained by researchers are analyzed with the stages of data collection, data selection, data reduction, and drawing conclusions. The conclusion in this article show that women have more flexible skills, are more careful, have a higher level of concern, and have a higher level of immunity compared to men. The advantages that women have should be utilized as well as possible so that they can be involved in government, state and private companies, and other groups to improve good corporate governance in the scope of government, companies, and other groups which can ultimately work together in creating Indonesia EMAS 2045. Involvement to achieve Indonesia EMAS is in line with the spirit of feminism and gender.